SafeTicket: Tickets Sale Safely Supported by Blockchain and NFTs - Gómez, Brandon (2024)
Ticketing systems act as ticket providers for various events such as plays, concerts, and sports competitions, among others. These tickets represent the right to attend the event, so their distribution, trading, and protection are important for users. However, current ticket sales processes do not fully consider user protection in secondary markets, leading to price speculation and, in more extreme cases, scams through ticket reselling. In response to this, we propose a ticketing system that aims to ensure transactions regarding ticket trading, using the distributed nature of a blockchain architecture, and NFTs (Non-Fungible Tokens) for this purpose. Additionally, the system includes the involvement of secondary markets through direct ticket transactions between users. As a result, SafeTicket was born, a mobile application supported by blockchain and non-fungible tokens. Finally, it was evaluated with a group of users, resulting in a high acceptance rate of the proposal.